Phenomenon of the Resonance Power Absorption in Multimode Waveguide-Dielectric Resonators - Minakova, L. B.; Rud, L. A. (Видавничий дім «Академперіодика», 2013)
Based on exact numerical and adequate qualitative models a theory of the resonance power absorption in waveguide-dielectric resonators is developed. The phenomenon of total absorption has been found for the TE10-mode incident on a rectangular lossy-dielectric post in a rectangular waveguide at the frequency close to the degeneration frequency of the two higher-order natural oscillations of the post with different symmetry and comparable Q-factors.